2017
DOI: 10.4236/gep.2017.55004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microbiological Pollutants on School Indoor Air Quality

Abstract: Asthma is common in children with allergens and mould influencing the development of the disease. Since children spend most of their time outside their homes within the school environment, school indoor air quality can directly influence their respiratory health. This study aims to identify microbiological contaminants in Maltese schools. The association between contaminants, respiratory health and school characteristics has been analysed. Five primary schools were selected with 9 to 11 years old students part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
4
1
1
Order By: Relevance
“…However, the analysis of correlations between the concentrations of total dust in the air and the concentrations of fungi in school rooms did not show statistically significant relationships (p>0.05). The presented relations differ from those observed in other school environments (Fsadni et al 2017, Sheik et al 2015. The analysis of total dust concentrations measured in the outdoor background and indoors the tested objects also showed that they did not differ statistically significantly (Kruskal-Wallis test: p>0.05).…”
Section: Resultscontrasting
confidence: 99%
“…However, the analysis of correlations between the concentrations of total dust in the air and the concentrations of fungi in school rooms did not show statistically significant relationships (p>0.05). The presented relations differ from those observed in other school environments (Fsadni et al 2017, Sheik et al 2015. The analysis of total dust concentrations measured in the outdoor background and indoors the tested objects also showed that they did not differ statistically significantly (Kruskal-Wallis test: p>0.05).…”
Section: Resultscontrasting
confidence: 99%
“…Asthma is common in children with allergies. Since children spend most of their time in school, indoor air contamination can affect their pulmonary health [12].…”
Section: Introductionmentioning
confidence: 99%
“…The fungal genera predominating various indoor environments are Aspergillus, Penicillium, Fusarium, Alternaria, Cladosporium, Stachybotrys, Trichoderma, and yeasts like Candida spp. (137,154,168). They have frequently been related to hospitalacquired infections and exacerbation of respiratory symptoms (20,167).…”
Section: Fungimentioning
confidence: 99%